2008
DOI: 10.1038/modpathol.2008.46
|View full text |Cite
|
Sign up to set email alerts
|

Evolution from heterozygous to homozygous KIT mutation in gastrointestinal stromal tumor correlates with the mechanism of mitotic nondisjunction and significant tumor progression

Abstract: Activating mutation in KIT or platelet-derived growth factor-a can lead to gastrointestinal stromal tumors (GISTs). Eighty-four cases from two institutes were analyzed. Of them, 62 (74%) harbored KIT mutations, 7 of which are previously unreported. One exhibited duplication from both intron 11 and exon 11, which has not been reported in KIT in human cancer. A homozygous/hemizygous KIT-activating mutation was found in 9 of the 62 cases (15%). We identified three GIST patients with heterozygous KIT-activating mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 46 publications
2
25
0
Order By: Relevance
“…The fact that LOH was present in the high-risk lesion is in accordance with the previously reported association of LOH with aggressive clinical behavior (O'Riain et al, 2005;Chen et al, 2008;Kleinbaum et al, 2008). Chen et al (2008) demonstrated that the mechanism of LOH in GIST is caused by mitotic nondisjunction and not by the generally accepted mechanism of mitotic recombination, in agreement with our finding of deletion of the KIT locus by FISH. Both patients here reported achieved partial response to imatinib, an ATP analogue that inhibits KIT kinase activity and blocks the phosphorylation of downstream substratum involved in the signaling transduction pathway of this receptor.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The fact that LOH was present in the high-risk lesion is in accordance with the previously reported association of LOH with aggressive clinical behavior (O'Riain et al, 2005;Chen et al, 2008;Kleinbaum et al, 2008). Chen et al (2008) demonstrated that the mechanism of LOH in GIST is caused by mitotic nondisjunction and not by the generally accepted mechanism of mitotic recombination, in agreement with our finding of deletion of the KIT locus by FISH. Both patients here reported achieved partial response to imatinib, an ATP analogue that inhibits KIT kinase activity and blocks the phosphorylation of downstream substratum involved in the signaling transduction pathway of this receptor.…”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, this is the fifth case with hereditary GIST caused by a KIT germline mutation showing LOH in the tumor (Kim et al, 2005;O'Riain et al, 2005;Lasota and Miettinen, 2006;Kleinbaum et al, 2008). The fact that LOH was present in the high-risk lesion is in accordance with the previously reported association of LOH with aggressive clinical behavior (O'Riain et al, 2005;Chen et al, 2008;Kleinbaum et al, 2008). Chen et al (2008) demonstrated that the mechanism of LOH in GIST is caused by mitotic nondisjunction and not by the generally accepted mechanism of mitotic recombination, in agreement with our finding of deletion of the KIT locus by FISH.…”
Section: Discussionsupporting
confidence: 90%
“…29,[34][35][36] In serial samples from individual patients, Chen et al 36 have provided evidence that this occurs through mitotic nondysjunction, ie, failure of a chromosome 4 pair bearing the wild-type KIT allele to separate during mitosis, leaving one daughter cell with a single chromosome 4 containing the mutant KIT allele (uniparental monosomy). This correlates with increased mitotic activity and topoisomerase II expression.…”
Section: Kitmentioning
confidence: 99%
“…A common theme of such mutations is the acquisition of mutant allele specific imbalance (MASI) either because of copy number-neutral loss of heterozygosity or mutant allele amplification, particularly during disease progression. 1 For example, MASI affects epidermal GFR (EGFR) mutations in lung cancer and glioblastoma, 2 KIT mutations in gastrointestinal tumors, 3 and MPL mutations in myelofibrosis. 4 MASI of activated GFRs may accelerate disease through a simple gene-dosage effect, although it is also possible that loss of the wild-type (WT) protein enhances the impact of the mutant allele, for example, by enhancing formation of mutant homodimers.…”
Section: Introductionmentioning
confidence: 99%